Hubungan Hujan dan Limpasan Pada Sub DAS Kecil Penggunaan Lahan Hutan, Sawah, Kebun Campuran di DAS Kreo - Dewi Liesnoor Setyowati (Universitas Muhammadiyah Surakarta, 2010)
Tendency of land use conversion is followed by maximum discharge of Kreo River, but unknown land use type what which can race improvement of runoff. Purpose of the research is study the relation of rainfall runoff at forest, rice field, and mixed garden. Research about rainfall runoff study is including research type of experiment for purpose of descriptive, through observation of rain data and water level at small watershed with one land use types that is forest, rice field, and mixed garden. Instrument of rain and water level attached at small watershed during the rains 2007.Data analysis comprises analysis of stream hydrograph, rain analysis, stream coefficient, and statistic analysis as well. Big the so small runoff value is more determined by rainfall amounts happened non land use type. Number of big rains at one land use will yield big runoff also, while the same rainfall amounts at some land use types will yield varying runoff follows land use type and condition of soil At small watershed (less than 200 ha), the relation of rainfall (P) with direct runoff (DRO) has very strong correlation (R2 bigger than 0.7). Relation between rain intensity (I) with DRO; I with peak discharge (Qp); duration of rain (DR) with DRO; DR with Qp indicated weak reaction (R2 less than 0.3). It indicated there were many factors (more than 70%) which influenced the above mentioned relations. Runoff coefficient value at forest was 0,3566, mix forest was 0,4227, rice field was 0,6661, and mixed garden was 0,4227. Land ability to permeate in the forest (65%) is bigger than mixed garden (57%) and rice field (33%).